Pelatihan Regulasi Emosi untuk Meningkatkan Penyesuaian Sosial Siswa - M. Ahkam Alwi; Nurfitriany Fakhri (IPTEK: Jurnal Hasil Pengabdian kepada Masyarakat, 2022)
Abstract. The problem experienced by students is that many students are not able to adapt to the school environment. Emotional regulation training is conducted to overcome the problem of low social adjustment in students. Increased emotional regulation can give students positive perceptions so that students can maximize their positive potential. The research method is carried out by taking various approaches, namely interactive lectures, games related to social adjustment, role play. The results showed that emotional regulation training was effective in increasing students' social adjustment.Keywords: emotion regulation, social adjustment, students